Green Synthesis of Polyesters Using Surfactant Catalysts in Microemulsions: The Role of Micelle Shape and Aggregation on Polymer Formation - Vadilson Malaquias dos Santos; Fabricio Uliana; Rayanne Penha Wandenkolken Lima; Eloi Alves da Silva Filho (Orbital: The Electronic Journal of Chemistry)
In this study, we explored traditional methods commonly found in the literature to analyze how surfactants and polymers interact during the synthesis of polyesters in emulsion systems. The study justifies its focus on micellar catalysis by exploring its effectiveness and suggesting methods for enhancing the synergy among surfactants, reactants, and catalys. We looked at factors like surface tension, critical micelle concentration, micelle shapes, aggregation numbers, and interfacial phenomena in the process of macromolecular packing in emulsion polycondensation. A surfactant-water system consisting of dodecylbenzenesulfonic acid and sodium dodecyl sulfate was employed. Polyesters were prepared from glycerol, ethylene glycol, diethylene glycol, and dicarboxylic acids in a surfactant-water system under mild conditions ranging from 70-150 °C. FTIR and 1H NMR confirmed the esterification. Differential scanning calorimetry indicated no crystallinity and a glass transition temperature range of –53 to –46 °C, typical of soft matter. The resulting polymers had molecular weights ranging from 1180 – 6800 g/mol. We found that these polymer aggregate shapes are able to respond by changing their sizes, both in bulk and at the air-solution interface, when the concentration of surfactant is increased above the critical micelle concentration. The results showed narrow spherical and ellipsoidal polymer aggregates, and the system was found to be suitable for green chemistry applications.